EFFECT OF MOTHERWORT TOTAL ALKALOIDS ON A TESTOSTERONE PROPIONATE-INDUCED ACNE: MOUSE MODEL - M. S. Miao; L. Guo; S. Tian (Journal of Animal and Plant Sciences, 2015)
We aimed to investigate the effect of motherwort total alkaloids (MTAs) on an acne mouse model induced by injection of testosterone propionate. High, medium and low dose of MTAs was each given to different mouse groups. The content of testosterone (T) in serum was determined. The morphological changes of testes, epididymides and seminal vesicles after each treatment were detected. Compared with the model control group, the mice treated with high, medium and low dose of MTAs had significantly different (P<0.05) content of serum T. Among tested groups, the MTA high dose group showed the most significant difference (P<0.01). The testis, epididymis and seminal vesicle weight of mice in each MTA group was decreased and the reduction was significantly different (P<0.05). The MTA high and medium dose groups had most significant difference (P<0.01). Motherwort herb promoted generation of various spermatogonial cells and increased sperm production in the seminiferous tubules of the testes. The higher the dosage was, the more effective MTAs were. Moreover, MTAs improved the function of epithelial cells in the epididymis tubule. High and low dose of MTAs had better effect. MTAs have a therapeutic effect on the acne mouse model.
Keywords: Motherwort total alkaloids; Acne; Mouse model